Strategi Resistensi dan Bertahan dalam Pandemi: Parade Cosplay Hantu di Desa Ngrengket Kabupaten Nganjuk - Ahmad Al Amin Putra; Shuri Mariasih Gietty Tambunan; Yudi Bachrioktora (Ideas Publishing, 2023)
Government utilized outbreak s fear to construct obedience, it was similar to Nganjuk’s Government. Nganjuk’s society experienced a repression during this situation, they were not be able to do their daily collective activities. This research is aimed unpacked analysis of society’s strategy during the repressive situation during the existence of PSBB policy. Ethnography and interview was conducted to recognize the aspects and details, also descriptive qualitative research are used in order to build a fundamental arguments. The result showed that Karang Taruna Cahaya Indah Rembol produced (encoding) and interpreted (decoding) ghost cosplay parade as a strategy to deceive PSBB policy. Those process are the forms of resistence and resilience toward PSBB policy or goverment as stakeholders. Kata kunci: masyarakat desa; pandemi; modernisme; spiritualisme; dan lokalitas